2019
DOI: 10.48550/arxiv.1910.13156
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Invasion and fixation of microbial dormancy traits under competitive pressure

Abstract: Microbial dormancy is an evolutionary trait that has emerged independently at various positions across the tree of life. It describes the ability of a microorganism to switch to a metabolically inactive state that can withstand unfavorable conditions. However, maintaining such a trait requires additional resources that could otherwise be used to increase e.g. reproductive rates. In this paper, we aim for gaining a basic understanding under which conditions maintaining a seed bank of dormant individuals provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(26 citation statements)
references
References 13 publications
(20 reference statements)
2
24
0
Order By: Relevance
“…Note that the detailed results behind D 1 have recently been established in [BT20]. The results related to D 2 will be a corollary to the results on mixed populations exhibiting dormancy and HGT in the present paper, see Section 3.…”
Section: Introductionsupporting
confidence: 58%
See 4 more Smart Citations
“…Note that the detailed results behind D 1 have recently been established in [BT20]. The results related to D 2 will be a corollary to the results on mixed populations exhibiting dormancy and HGT in the present paper, see Section 3.…”
Section: Introductionsupporting
confidence: 58%
“…[KKL01, TLLPS11, BGKW16, BGKW20]), they have only rather recently been considered in a population dynamics framework involving direct competition. Indeed, in our recent preprint [BT20], we introduced an individual-based model for the invasion analysis of a dormancy trait in a resident population lacking this trait. We showed that under suitable assumptions on the model parameters, with asymptotically positive probability, a newly arriving ('mutant') individual having the dormancy trait is able to invade a resident population, even if it has a significantly lower reproductive rate than the residents, and in case of a successful invasion, it will fixate with high probability.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations